Does foreign aid promote growth? Evidence from Africa. (8th February 2023) - Abou-Zaid, Ahmed; Alghamdi, Mai; Alabdulwahab, Sami; Shahawy, Shimaa Al
This study investigates the impact of foreign aid policies on several African countries and their interaction with economic growth. Panel data analysis has been implemented for 54 African countries. The pooled, GLS and random effect methods have been incorporated to capture the impact of the foreign aid policies over economic growth. The study uses World Bank countries classification based on income. Furthermore, the countries have been divided into three groups based on income level. Our findings show that foreign aid has a positive significant impact, with minimal effect on economic growth. Also, the aid-growth relationship is non-linear and foreign aid has diminishing returns as the volume of aid increases. However, the rise of foreign aid dependence will create a moral hazard. This outcome is a consequence of channelling foreign aid to finance the service of standing debts instead of financing development projects.